Population education: concept, theory and location within the educational system - شاهين , سيلين; مدى شريقي (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The demographic crisis, which was associated with the rapid population growth witnessed by the humanity during long decades; was a central subject of interest for all the Population education: concept, theory and location within the educational systemcountries of the world in general, and in the developing countries in particular. This is due to the importance of the population aspect in the planning and in social and economic development. Indeed, some problems have exacerbated and turned into deep-rooted crises represented by a population environmental crisis, which was reflected in the lack of food, water, education and proper health care; and in the high rates of pollution and the expansion of deserts, and the decrease in natural resources, in addition to the aggravation of the problem of housing and unemployment and the pressure of the migration movements from the poorest countries towards the developed countries, and other repercussions that necessitated finding radical solutions to this continuous pressure on services and resources, and the need to go more towards building the individual human being, and to achieve development by him and through him. All of this made researchers and workers in the population field turn to link the population issue with the educational process in an emerging step to spread population awareness through the educational process. If the plans of the past did not succeed in achieving a balance between the environmental resources and the satisfaction of population needs in a way that ensures the continuity of these resources for future generations, and that the population obtains the basic needs without shortage; then hopefully it may succeed in the future through this new approach.